2012
DOI: 10.5152/jarem.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Escherichia coli Strains Isolated in Community Acquired Urinary Tract Infections

Abstract: ÖZETAmaç: Bu çalışmada, İstanbul'da bir özel hastanede toplum kökenli üriner sistem enfeksiyonlarından izole edilen Escherichia coli suşlarında antimikrobiyal duyarlılıklarının belirlenmesi amaçlanmıştır. Results: A total of 191 E. coli strains isolated from urine cultures which were processed between January 2008 and December 2008 in the clinical laboratory, were included in the study. Identification of bacteria and antibiotic susceptibility tests were performed by disk diffusion and automated system. Of E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…In a study conducted by Gozukucuk et al in Istanbul,191 E. coli strains were isolated and the resistance rates were found to be 40% in trimethoprim-sulfamethoxazole, 19.8% in ciprofloxacin, 19.2% in ceftriaxonde and 12.4% in nitrofurantoin (14). In our study, nitrofurantoin resistance with 5.8% was lower than this study, whereas, Ciprofloxacin resistance was higher with 34.1%.…”
Section: Discussioncontrasting
confidence: 64%
“…In a study conducted by Gozukucuk et al in Istanbul,191 E. coli strains were isolated and the resistance rates were found to be 40% in trimethoprim-sulfamethoxazole, 19.8% in ciprofloxacin, 19.2% in ceftriaxonde and 12.4% in nitrofurantoin (14). In our study, nitrofurantoin resistance with 5.8% was lower than this study, whereas, Ciprofloxacin resistance was higher with 34.1%.…”
Section: Discussioncontrasting
confidence: 64%
“…reported that positive urine culture was detected in 348 of 1493 patients visiting the outpatient clinic due to UTI and E. coli was the main causative agent in 54.8% of the cases. [ 19 ] According to the urine culture and antibiogram reports, they detected sensitivity rates as; 36.3% for ampicillin, 80.2% for ciprofloxacin, and 87.6% for nitrofurantoin. [ 19 ] In a retrospective study, Pekdemir et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] According to the urine culture and antibiogram reports, they detected sensitivity rates as; 36.3% for ampicillin, 80.2% for ciprofloxacin, and 87.6% for nitrofurantoin. [ 19 ] In a retrospective study, Pekdemir et al . detected positive urine culture in 90 of 257 patients admitted to the ED, and they identified E. coli as the most common agent (57.8%), and antibiotic susceptibility to E. coli was reported as; 51.9% for ciprofloxacin, 34.6% for ampicillin, and 85.3% for nitrofurantoin.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, TMP-SXT resistance varies from 20% to 60% for E. coli strains isolated from community-acquired urinary tract infections (Table 4) [8,9,[13][14][15][16]. Because of the high TMP-SXT resistance, it seems that TMP-SXT has not been included in the prescriptions arranged by our polyclinics in accordance with the recommendations of guidelines.…”
Section: Discussionmentioning
confidence: 99%